Evaluation of Wastewater Coagulation/Flocculation with Chitosan from Shrimp Exoskeletons Waste and Aluminum Sulfate - Labastida-Núñez, Israel; Velasco-Pérez, Maribel; Pablo-Reyes, Elia Piedad; González-Aragón, Abelardo; Beltrán-Villavicencio, Margarita (REVISTA TERRA LATINOAMERICANA, 2023)
Intensive use of water, growing cities, and lack of wastewater treatment are some factors increasing hydric stress worldwide. Coagulation/flocculation is one of the preferred treatments for wastewater. However, aluminum salts are traditionally used in this process. This coagulant has a high environmental footprint and residual aluminum in wastewater is a public health concern. The preparation and use of chitosan as a coagulant aid in coagulation/flocculation with aluminum sulfate were investigated. The ef fect of the order of addition of coagulants (aluminum sulfate followed by chitosan, or chitosan followed by aluminum sulfate), dose of the coagulants, pH, and slow mixing velocity for flocculation were studied. It was found that the removal of total suspended solids (TSS) with aluminum sulfate was relatively unaf fected by pH (aluminum sulfate dose of 100 mg L-1 at pH of 5 units achieved 94% removal of TSS and at pH of 8.2 units 89% removal of TSS), whereas with chitosan was highly af fected (chitosan dose of 180 mg L-1 at pH of 4 units achieved 96% removal of TSS and at pH of 8.2 units 25% removal of TSS). In the coagulation/flocculation experiments where both coagulants were used, it was found that the order of coagulant addition and pH of wastewater have a statistically significant ef fect (P-value < 0.05) on the removal of TSS. Higher removal of TSS was achieved when aluminum sulfate was added followed by chitosan at a wastewater pH of 5 units. Chitosan can be ef fectively used to reduce the use of aluminum salts in wastewater treatment. However, it is necessary to optimize the preparation of this coagulant and investigate other factors, such as variation in the wastewater quality, that can af fect the robustness of the process.